Use of Two Self-referral Reminders and a Theory-Based Leaflet to Increase the Uptake of Flexible Sigmoidoscopy in the English Bowel Scope Screening Program: Results From a Randomized Controlled Trial in London. Issue 11 (15th January 2018) - Kerrison, Robert S; McGregor, Lesley M; Counsell, Nicholas; Marshall, Sarah; Prentice, Andrew; Isitt, John; Rees, Colin J; von Wagner, Christian
Abstract: Background: We previously initiated a randomized controlled trial to test the effectiveness of two self-referral reminders and a theory-based leaflet (sent 12 and 24 months after the initial invitation) to increase participation within the English Bowel Scope Screening program. Purpose: This study reports the results following the second reminder. Methods: Men and women included in the initial sample ( n = 1, 383) were re-assessed for eligibility 24 months after their invitation (12 months after the first reminder) and excluded if they had attended screening, moved away, or died. Eligible adults received the same treatment they were allocated 12 months previous, that is, no reminder ("control"), or a self-referral reminder with either the standard information booklet ("Reminder and Standard Information Booklet") or theory-based leaflet designed using the Behavior Change Wheel ("Reminder and Theory-Based Leaflet"). The primary outcome was the proportion screened within each group 12 weeks after the second reminder. Results: In total, 1, 218 (88.1%) individuals were eligible. Additional uptake following the second reminder was 0.4% (2/460), 4.8% (19/399), and 7.9% (29/366) in the control, Reminder and Standard Information Booklet, and Reminder and Theory-Based Leaflet groups, respectively. When combined with the first reminder, the overall uptake for each group was 0.7% (3/461), 14.5% (67/461), and 21.5% (99/461). Overall uptake was significantly higher in the Reminder and Standard Information Booklet and Reminder and Theory-Based Leaflet groups than in the control (odds ratio [OR] = 26.1, 95% confidence interval [CI] = 8.1–84.0, p < .001 and OR = 46.9, 95% CI = 14.7–149.9, p < .001, respectively), and significantly higher in the Reminder and Theory-Based Leaflet group than in the Reminder and Standard Information Booklet group (OR = 1.8, 95% CI = 1.3–2.6, p < .001). Conclusion: A second reminder increased uptake among former nonparticipants. The added value of the theory-based leaflet highlights a potential benefit to reviewing the current information booklet. Trials Registry Number: ISRCTN44293755. Abstract : Reminder letters, which prompt 'no-shows' to self-refer for bowel cancer screening, increase uptake and thereby the total number of pre-cancerous lesions detected.